The Bright Side and the Dark Side of Scopolamine (Pharmacology, Toxicology, and Clinical Use Review) (Journal of Science and Technology Research for Pharmacy, 2022)
Scopolamine is one of tropane alkaloids obtained from Solanaceae plants. This compound has been used for a long time by human for both good and bad cause, such as dilating pupil, analgesic, anaesthesia, and even poisoning or other criminal acts. Scopolamine possess many pharmacological activities due to its anticholinergic activity. It binds non-selectively to muscarinic receptors both peripherally and centrally. At therapeutic dose, scopolamine may be beneficial for preventing motion sickness and Post Operative Nausea and Vomiting (PONV), treating sialorrhea in disabled patients, lowering depression, and preventing death rattle. However, its effect on anxiety level is still conflicting. Adverse effects commonly occurred at therapeutic dose is usually tolerable, such as sedation, dry mouth, skin reactions, blurred vision, mydriasis, and confusion. At higher dose, scopolamine may generate harmful effects, such as amnesia, delirium, hallucination, hypertension, tachycardia, and arrythmia. For its effect on memory and sedative effect, scopolamine is frequently used in some countries, such as Columbia and Indonesia recently to incapacitating victims. Treatment for poisoning of scopolamine is usually supportive to treat symptoms. Antidote use, acetylcholinesterase inhibitor, such as physostigmine may be used in certain condition.